MODEL STRUKTUR SUBDUKSI KERAK DI PERAIRAN LAUT MALUKU DAN VULKANISME BERDASARKAN ANALISIS GAYA BERAT DAN KEGEMPAAN - B. Setyanta; I. Setiadi (Pusat Survei Geologi, 2011)
Volcanic arc in Maluku Sea area with relative north-south trend, in the North Arm of Sulawesi consists of Taguladong, Biaro, Bangka, Sangihe islands, and west part of Halmahera are Ternate, Makian, Kayoa and Tidore islands. Bouguer anomaly in this area shows the line patterns that trend to be north-south, in same direction of the pattern of the regional geological structures with the anomaly value range (-100 mGal until 260 mGal). Gravity modelling analysis indicate the presence of subduction beneath the islands of Halmahera is tilted to the east with a steep, while in the western part which is below the north arm of Sulawesi is not visible. Structure pattern of gravity analysis show strike slip fault system in the west part, and thrust fault in the east part that controlling volcanism activity in this area.Keyword: